Haemodynamic and catecholamine response to simulated ventricular tachycardia in man: effect of baseline left ventricular function. (1st March 2003) - Kolettis, T M; Psarros, E; Kyriakides, Z S; Katsouras, C S; Michalis, L K; Sideris, D A
Abstract : Objective: To examine the effects of baseline left ventricular function on the haemodynamic and catecholamine responses to ventricular tachycardia. Design: Experimental cohort study. Setting: Cardiac catheterisation laboratory in tertiary referral centre. Subjects: 24 patients (19 male, 5 female; mean (SD) age, 59 (10) years) without coronary artery disease, divided into two groups with normal or impaired left ventricular function: group A, ejection fraction > 65% (n = 10); group B, ejection fraction < 45% (n = 14). Other medical and demographic factors were similar in the two groups. Interventions: Ventricular tachycardia was simulated with rapid pacing at 150 beats/min for 10 minutes. Main outcome measures: Arterial blood pressure; venous plasma catecholamine concentrations. Results: During rapid pacing, blood pressure was lower in group B (with impaired left ventricular function) than in group A: systolic blood pressure, 102 (11) v 115 (9) mm Hg (p = 0.005); mean blood pressure, 79 (6) v 85 (6) mm Hg (p = 0.02). The ejection fraction correlated with the lowest systolic blood pressure ( r = 0.64, p = 0.0006). Although the rise in adrenaline was comparable between the two groups, the rise in noradrenaline was more pronounced (p < 0.05) in patients in group B. Conclusion: At low rates and in selected patients, the underlying state of left ventricular function affects haemodynamic tolerance of ventricular tachycardia. Patients with impaired left ventricular function have a lower blood pressure during ventricular tachycardia, despite an exaggerated noradrenaline release.